An elephant in the garden - Morpurgo, Michael (Square Fish, 2013)
In Dresden, Germany during World War II, a zookeeper gets permission to bring an elephant that's bonded with her children home to stay in her garden until the bombing of the city stops. When their home is destroyed next, the zookeeper, her children, and the elephant are forced to flee Russian soldiers in the dead of winter.